The Comparison of Oral and Intravaginal Administration of Lactobacillus plantarum Probiotics on Body Weight of Rattus norvegicus with Vulvovaginalis Candidiasis - Matin, Nur Sophia; Fristiyanti, Regina Ayu (Jurnal Penelitian Keperawatan Kontemporer, 2025)
Background: The prevalence of fungal infections in humans has been recorded to have increased significantly. Several species of fungi in the genus Candida are reported to cause mucosal and systemic infections with high levels of morbidity and mortality. Infections caused by Candida are called candidiasis, one type of which is Vulvovaginal Candidiasis (Vulvovaginal Candidiasis). In the last few decades, Lactobacillus probiotics have become an alternative strategy for treating various types of infections, including L. plantarum. The comparison of effectiveness between oral and intravaginal administration of L. plantarum still needs to be studied, considering that this really determines the success rate of probiotics as supportive therapy in cases of vulvovaginal candidiasis. Objective: To compare body weight gain after oral and intravaginal administration of L. plantarum in vivo. Method: The research was conducted using a pretest posttest randomized experimental group design approach. The L. plantarum given consisted of three concentrations, namely 2,25x1010, 4,5x1010 and 9x1010 CFU/ml. The statistical analysis used was a paired T-test (CI 95%) to measure body weight before and after administration of L. plantarum. Results: There was a significant increase in the body weight of the study sample with oral and intravaginal administration. Conclusion: Probiotic L. plantarum given orally and intravaginally has the potential to be a supportive therapy for vulvovaginal candidiasis infections.